Formulasi dan Evaluasi Fisik Sediaan Sunscreen Powder Zink Oksida - Latifah, Fadzil; Sholeh, Aries Badrus; Dharmawan, Jelshe Reada (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Zinc Oxide (ZnO) is a white sunscreen ingredient used to protect the skin layer from exposure to ultraviolet rays so that it can be used as an active ingredient in sunscreen. Powdered sunscreen preparations are fine and light powders that can provide a thin layer on the skin so that they are effective when used for faces with makeup. The purpose of this study was to formulate and provide physical preparations of zinc oxide powdered sunscreen with varying concentrations to see the best physical characteristics. Methods: This research is experimental in nature using 3 variations of zinc oxide concentrations of 5% (F1), 10% (F2), and 15% (F3) by evaluating the physical preparation including organoleptic tests, homogeneity tests, pH tests, fineness tests and stability tests. Results: The results of this study were obtained in the three formulas having the physical characteristics of a typical rosae odor, yellowish white in color, smooth texture, homogeneous dispersed powder, and stable in storage. In the pH test of sunscreen powder preparations, the concentration variations F1, F2, and F3 each obtained pH values of 5.24: 6.67, 7.31 respectively so that F3 meets the requirements for skin pH values in the range of 4 - 5.5. Conclusion: This study can conclude that the sunscreen powder that has the best characteristics is formula 1 with a zinc oxide concentration of 5%.